Association Between Arterial Oxygen Saturation and Lung Ultrasound B-Lines After Competitive Deep Breath-Hold Diving - Patrician, Alexander; Pernett, Frank; Lodin-Sundström, Angelica; Schagatay, Erika (Frontiers in Physiology, 2021)
Breath-hold diving (freediving) is an underwater sport that is associated with elevated hydrostatic pressure, which has a compressive effect on the lungs that can lead to the development of pulmonary edema. Pulmonary edema reduces oxygen uptake and thereby the recovery from the hypoxia developed during freediving, and increases the risk of hypoxic syncope. We aimed to examine the efficacy of SpO2, via pulse-oximetry, as a tool to detect pulmonary edema by comparing it to lung ultrasound B-line measurements after deep diving. SpO2 and B-lines were collected in 40 freedivers participating in an international deep freediving competition. SpO2 was measured within 176 min and lung B-lines using ultrasound within 4415 min after surfacing. A specific symptoms questionnaire was used during SpO2 measurements. We found a negative correlation between B-line score and minimum SpO2 (rs= -0.491; p=0.002) and mean SpO2 (rs= -0.335; p=0.046). B-line scores were positively correlated with depth (rs=0.408; p=0.013), confirming that extra-vascular lung water is increased with deeper dives. Compared to dives that were asymptomatic, symptomatic dives had a 27% greater B-line score, and both a lower mean and minimum SpO2 (all p<0.05). Indeed, a minimum SpO2 ≤ 95% after a deep dive has a positive predictive value of 29% and a negative predictive value of 100% regarding symptoms. We concluded that elevated B-line scores are associated with reduced SpO2 after dives, suggesting that SpO2 via pulse oximetry could be a useful screening tool to detect increased extra-vascular lung water. The practical application is not to diagnose pulmonary edema based on SpO2 – as pulse oximetry is inexact – rather, to utilize it as a tool to determine which divers require further evaluation before returning to deep freediving.